CTNI-58. A PROSPECTIVE TRIAL OF RESECTION AND SURGICALLY TARGETED RADIATION THERAPY FOR INITIAL OR SALVAGE TREATMENT OF AGGRESSIVE MENINGIOMA. (9th November 2020) - Rogers, Leland; Nakaji, Peter; Youssef, Emad; Smith, Kris; Thomas, Terry; Zabramski, Joseph; Dardis, Christopher; Pinnaduwage, Dilini; McBride, Heyoung; Brachman, David
Abstract: INTRODUCTION: Achieving durable local control (LC) for aggressive or recurrent meningiomas remains problematic. Resection (R) alone is insufficient and even with the addition of radiation therapy (RT), outcomes are suboptimal in many series. OBJECTIVE: Hypothesizing R plus Surgically Targeted Radiation Therapy (STaRT) may improve LC, we evaluated a permanently implanted brachytherapy device consisting of Cs-131 seeds positioned within modular resorbable collagen carrier/spacer tiles (GammaTile, GT Medical Technologies, Tempe AZ). METHODS: From 2/2013-2/2018 recurrent and newly diagnosed aggressive meningiomas were treated on a prospective single-arm study (NCT#03088579). At completion of maximum safe resection the tumor bed was lined with collagen tiles imbedded with Cs-131, delivering 60–80 Gy at 5 mm depth. No additional local therapy was given absent progression. RESULTS: 35 meningiomas in 28 patients were treated; 29 recurrent (22 prior R+RT, 6 R only, and 1 RT only) and 6 without prior therapy. WHO grade was I in 2 patients, II in 28, and III in 5. Median age was 66 years (range 37–82), KPS 80 (70–100), female: male ratio 15:13. Mean time for implantation was 5 minutes. At a median radiographic follow-up of 25.5 months (range 0.1–71) LC was 80% (28/35) and median time to progression had not been reached (95% CI > 35.6 months). LC at 12/24/36/48 months was 100/89/72/72% for all tumors, 100/93/79/79% for Grade II, and 100/50/0/0% for Grade III, respectively. No patient receiving STaRT as their initial RT failed. Median overall survival was 50 months. Four symptomatic adverse events occurred, 2 wound breakdowns requiring surgery and 2 radiation-related brain changes, medically treated. CONCLUSION: R+STaRT demonstrates favorable safety and LC outcomes in this single-arm prospective trial that includes heavily pre-treated patients. A commercial version of the device recently received FDA clearance for use in newly diagnosed malignant or recurrent intracranial neoplasms including meningiomas.